Intein mediated high throughput screening for bispecific antibodies. Issue 1 (1st January 2020) - Hofmann, Tim; Schmidt, Johannes; Ciesielski, Elke; Becker, Stefan; Rysiok, Thomas; Schütte, Mark; Toleikis, Lars; Kolmar, Harald; Doerner, Achim
ABSTRACT: Bispecific antibodies comprise extremely diverse architectures enabling complex modes of action, such as effector cell recruitment or conditional target modulation via dual targeting, not conveyed by monospecific antibodies. In recent years, research on bispecific therapeutics has substantially grown. However, evaluation of binding moiety combinations often leads to undesired prolonged development times. While high throughput screening for small molecules and classical antibodies has evolved into a mature discipline in the pharmaceutical industry, dual-targeting antibody screening methodologies lack the ability to fully evaluate the tremendous number of possible combinations and cover only a limited portion of the combinatorial screening space. Here, we propose a novel combinatorial screening approach for bispecific IgG-like antibodies to extenuate screening limitations in industrial scale, expanding the limiting screening space. Harnessing the ability of a protein trans-splicing reaction by the split intein Npu DnaE, antibody fragments were reconstituted within the hinge region in vitro . This method allows for fully automated, rapid one-pot antibody reconstitution, providing biological activity in several biochemical and functional assays. The technology presented here is suitable for automated functional and combinatorial high throughput screening of bispecific antibodies.